A Comparison of Parapoxviruses in North American Pinnipeds - Costa, Helena; Klein, Jörn; Breines, Eva M.; Nollens, Hendrik H.; Matassa, Keith; Garron, Mendy; Duignan, Padraig J.; Schmitt, Todd; Goldstein, Tracey; Tryland, Morten (Frontiers in Veterinary Science, 2021)
Parapoxviruses cause nodular lesions on the skin and mucosal membranes of pinnipeds and infections by these viruses have been documented worldwide. Seal parapoxvirus is currently classified as a tentative species of the Parapoxvirus genus. Tissue or swab samples were analyzed from 11 pinnipeds of different host species undergoing rehabilitation on the east and west coasts of the United States of America (USA) that were positive for parapoxvirus. The aim of the study was to compare parapoxvirus sequences of fragments of the B2L, DNA polymerase, GIF and viral interleukin-10 orthologue (vIL-10) genes and to examine the evolutionary relationship between viruses detected in different pinniped species and at different locations with other members of the Parapoxvirus genus, such as Orf virus (ORFV), Bovine papular stomatitis virus (BPSV) and Pseudocowpox virus (PCPV). The sequence analysis showed that the parapoxvirus sequences from the pinnipeds differed significantly from those found in terrestrial hosts and that they formed a separate cluster within the genus. Our results suggest that transmission of the same parapoxvirus strain is possible between different species, including between members of different families (phocids and otariids). Animals belonging to the same species but living in distant geographic locations presented genetically distant parapoxviruses. The findings of this study demonstrate that sealpox lesions in pinnipeds of different species are caused by viruses that belong to the Parapoxvirus genus but have significant genetic differences compared to the established species in terrestrial species thus strongly supporting the classification of pinniped parapoxvirus as a new species of the genus.